2020
DOI: 10.1055/s-0040-1721220
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Observational Study Comparing Long-Course Conventional Neoadjuvant Chemoradiotherapy with Short-Course Radiotherapy Followed by Consolidation Chemotherapy with Delayed Surgery in Locally Advanced Rectal Cancer

Abstract: Background Polish and Australian randomized studies compared short-course radiotherapy (RT) with immediate surgery and long-course chemoradiotherapy (CRT) with delayed surgery. In these studies, similar long-term survival and local control have been reported for both these approaches, but pathological complete response (pCR) is not better with short-course RT. Moreover, studies have shown better tumor downstaging with delayed surgery. In this context, the use of short-course RT with delayed surgery may have so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
(15 reference statements)
1
7
0
Order By: Relevance
“…Fig 1 shows the selection of relevant studies for inclusion in the meta-analysis. A total of 8 nRCTs with 1502 and 7 RCTs with 2077 enrolled patients enrolled patients were included for this meta-analysis [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] (Fig 1), there were 1812 patients in the TNT group and 1767 patients in the nCRT group. The main characteristics of the included studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Fig 1 shows the selection of relevant studies for inclusion in the meta-analysis. A total of 8 nRCTs with 1502 and 7 RCTs with 2077 enrolled patients enrolled patients were included for this meta-analysis [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] (Fig 1), there were 1812 patients in the TNT group and 1767 patients in the nCRT group. The main characteristics of the included studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…1 ). Four of these studies were RCTs [ 9 , 17 19 ], and the other three were non-RCTs [ 20 22 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…2, which demonstrated risk of bias graph and risk of bias summary). The three non-RCTs were all cohort studies including two prospective study [ 20 , 22 ] and one retrospective study [ 21 ]. All three cohort studies scored at least 6 based on the Newcastle–Ottawa criteria (Additional file 1 : Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies enrolling 7507 rectal cancer patients from 13 cohorts were included in this meta-analysis [13][14][15][16][20][21][22][23][24][25][26][27][28][29][30][31][32]. Of these, two studies reported different parameters of the same cohort [28,29], four studies reported survival outcomes at different time points [13,14,20,24], and one study reported an expanded enrollment including the preliminary cohort [31].…”
Section: Characteristics Of the Included Studymentioning
confidence: 99%
“…All studies were published between 2015 and 2022; of these, ten were RCTs, two were prospective studies, and five were retrospective studies. In summary, four cohorts from five studies compared SCRT with delayed surgery (n = 803) and conventional CRT (n = 4075) [13,[20][21][22][23], and nine cohorts from 12 studies compared SCRT followed by consolidation chemotherapy with delayed surgery (n = 1452) and conventional CRT (n = 1452) [14][15][16][24][25][26][27][28][29][30][31][32]. The characteristics of the included studies are summarized in Table 1.…”
Section: Characteristics Of the Included Studymentioning
confidence: 99%